(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The development of human capital in Uzbekistan envisions innovative progress, sustainable growth of our country, socio – economic advancement and high- level training of resources. Investing in human capital means investing in the future. The article highlights the relevance of human capital development in the Republic of Uzbekistan and its role in economic and social progress. The article analyzes the reforms being implemented in the main components of human capital education and upbringing, healthcare, skills and qualifications, as well as the development of professional competencies. It also justifies the need to strengthen the education system based on modern knowledge and technologies, and to enhance innovative potential as priority directions. Therefore, one of the main ideas in the implementation of the “Uzbekistan-2030” strategy is the development of human capital, which envisionsthe creation of education, healthcare, and social protection systems that fully meet the needs of the population and international standarts.